2004
DOI: 10.3402/tellusa.v56i5.14599
|View full text |Cite
|
Sign up to set email alerts
|

Arctic climate change: observed and modelled temperature and sea-ice variability

Abstract: A B S T R A C TChanges apparent in the arctic climate system in recent years require evaluation in a century-scale perspective in order to assess the Arctic's response to increasing anthropogenic greenhouse-gas forcing. Here, a new set of centuryand multidecadal-scale observational data of surface air temperature (SAT) and sea ice is used in combination with ECHAM4 and HadCM3 coupled atmosphere-ice-ocean global model simulations in order to better determine and understand arctic climate variability. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 5 publications
7
60
0
Order By: Relevance
“…[17] A question is whether the links reported here are robust. The period under study falls on the years of Arctic amplification of global warming [e.g., Johannessen et al, 2004] and the general intensification of the thermohaline conveyor in the North Atlantic [e.g., Zhang et al, 2004]. However, even in this period of strong Atlantic water inflow to the Nordic Seas, the interannual oceanic heat variability downstream of the Norwegian Atlantic Current depended more on the regional air-sea interactions than on the transport of heat anomalies from the south [Schlichtholz and Houssais, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…[17] A question is whether the links reported here are robust. The period under study falls on the years of Arctic amplification of global warming [e.g., Johannessen et al, 2004] and the general intensification of the thermohaline conveyor in the North Atlantic [e.g., Zhang et al, 2004]. However, even in this period of strong Atlantic water inflow to the Nordic Seas, the interannual oceanic heat variability downstream of the Norwegian Atlantic Current depended more on the regional air-sea interactions than on the transport of heat anomalies from the south [Schlichtholz and Houssais, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…There is no indication of multidecadal variability or reduced sea ice during the well-documented early twentieth century warming (ETCW) in the Arctic during the 1920s and 1930s in HADISST ( Figure S2 in the supporting information). However, there are local and regional historical observations that do show reduced sea ice during the ETCW [Johannessen et al, 2004], and a multidecadal mode of variability has been suggested [e.g., Polyakov et al, 2003] Moros et al, 2006;Macias Fauria et al, 2010;Kinnard et al, 2011] provide an opportunity to (1) robustly identify and track multidecadal sea-ice variability and (2) establish linkages to known climate system fluctuations on a multidecadal timescale [e.g., Delworth and Mann, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Recent temperature increases in the arctic and subarctic have been significantly greater than global averages and the North American western Arctic is one of the most rapidly warming regions on the planet [Johannessen et al, 2004;Serreze et al, 2000]. Permafrost temperatures are rising in response to 20th century climate warming in Alaska and northwestern Canada and the frequency and magnitude of terrain disturbances associated with thawing permafrost, including the degradation of ice wedges and lake shrinkage, is increasing [Jorgenson et al, 2006;Osterkamp and Romanovsky, 1999;Smith et al, 2005;Yoshikawa and Hinzman, 2003].…”
Section: Introductionmentioning
confidence: 99%